Information modelling for management - Bytheway, Andrew (Cranfield School of Management, 1995)
A review of the literature shows substantial interest in new ways of modelling business, and a tendency to adopt a process or technological perspective in so doing. The information perspective is less often used and can present difficulties in terms of achievement and acceptance by non-specialists. A new approach to business analysis incorporates entity modelling (as well as other techniques) and provides a more flexible approach than is normally applied. It allows different starting points to be chosen, including entity modelling as a means of brainstorming management's ideas about what comprises the fundamental aspects and building blocks of the business. Three case studies - based in manufacturing, retailing and systems services respectively - provided an opportunity to test the usefulness of this more flexible approach. By undertaking model building and reviews with senior management, outside the context of systems planning and requirements analysis, it is shown that there is an acceptable form of information modelling which is useful to managers. A general topological framework was derived through these case studies which provided resilient and helpful. A particular feature of the third case study is the extension of information modelling to permit the construction of a completely new process model for a new business. This has potential for development at a time when businesses are more and more likely to consider a "fresh start" as an alternative to the conventional development and improvement of established business units.